Socio-Cultural Meanings and Practices of Modernity Consumption of Ramyeon (Korean Instant Noodles) among Thai Youths - Changphao , Wichuda; Lertchavalitsakul, Busarin (Journal of Social Sciences Naresuan University, 2025)
Conceptually framed by modernity and practices of consumption, this article examines the socio-cultural meanings attributed to ramyeon (Korean instant noodles) by Thai youths and their practices of modernity consumption. It uses a qualitative research methodology comprising observations on social media platforms, and in-depth interviews with eleven individuals categorized into three groups: ramyeon social media content creators, online ramyeon sellers, and ramyeon consumers. The findings reveal that Thai youths associate three key socio-cultural meanings with ramyeon: it symbolizes Korean culture, offers a unique and exotic taste, and reflects a modern eating style that resonates with teenage consumers. The article argues that the popularity of ramyeon, fueled by social media, has fostered new consumption practices. These practices not only involve self-presentation but also content creation and product selling by both sellers and content creators as a means of communication with consumers. Ultimately, ramyeon has continually acted as a form of soft power of Korean culture.